2008
DOI: 10.2217/17410541.5.4.361
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacogenetic Testing of Cyp2D6 in Patients with Aripiprazole-Related Extrapyramidal Symptoms: A Case–Control Study

Abstract: Aripiprazole is primarily metabolized by the polymorphic CYP2D6. We genotyped four children (aged 6-15 years) who had developed extrapyramidal symptoms within 1 week of aripiprazole initiation or dose titration, and four matched children without extrapyramidal symptoms. All of the four children who developed extrapyramidal symptoms with aripiprazole had a dysfunctional CYP2D6 enzyme, based on genotype, and were categorized as either intermediate metabolizers (n = 2) or poor metabolizers (n = 2). By contrast, o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Template taken from Page et al, 2021). The reasons for excluding the records included insufficient information on weight or BMI (Inada et al, 2003;Plesnicar et al, 2006;Subuh Surja et al, 2008) and ineligible study population such as healthy volunteers receiving a single drug dose (Sun et al, 2019) or schizophrenic patients with acute episodes who were on antipsychotic medication for less than one month before weight measurement (Vandenberghe et al, 2015). Some had genotyped some CYP2D6 single nucleotide polymorphisms (SNPs) but, unfortunately, these selected SNPs did not allow us to call for CYP2D6 alleles and classify participants into CYP2D6 metabolic groups (Lee et al, 2012).…”
Section: Literature Searchmentioning
confidence: 99%
“…Template taken from Page et al, 2021). The reasons for excluding the records included insufficient information on weight or BMI (Inada et al, 2003;Plesnicar et al, 2006;Subuh Surja et al, 2008) and ineligible study population such as healthy volunteers receiving a single drug dose (Sun et al, 2019) or schizophrenic patients with acute episodes who were on antipsychotic medication for less than one month before weight measurement (Vandenberghe et al, 2015). Some had genotyped some CYP2D6 single nucleotide polymorphisms (SNPs) but, unfortunately, these selected SNPs did not allow us to call for CYP2D6 alleles and classify participants into CYP2D6 metabolic groups (Lee et al, 2012).…”
Section: Literature Searchmentioning
confidence: 99%
“…We also assessed genetic variations in the CYP2D6, CYP3A4, and CYP3A5 genes that encode enzymes involved in the metabolism of ARI. It is postulated that nonfunctional alleles are associated with potential adverse effects [18] and extrapyramidal reactions, nausea, or vomiting are more frequently observed in IM and PM patients treated with ARI [5,19]. Surprisingly, in both our studied groups, the frequency of functional alleles (*1 plus *2) was similar and accounted for more than 60%, while the frequency of CYP2D6-defective alleles was more than two times higher in the ARI compared to the ARI-ADE group (29% vs. 13%, respectively).…”
Section: Resultsmentioning
confidence: 99%
“…Hendset et al [ 98 ] observed that CYP2D6 -defective alleles patients were associated with more potent adverse effects. In addition, a case–control study with eight patients suggested that IM and PM CYP2D6 status are more frequently associated with extrapyramidal reactions [ 108 ]. Another study found that PM and IM were associated with higher incidence of nausea/vomiting due to higher plasma concentrations of aripiprazole in these subjects [ 101 ].…”
Section: Long-acting Aripiprazolementioning
confidence: 99%